Normothermic Ex-Vivo Kidney Perfusion Restores the Genetic Profile of Marginal Kidney Grafts Subjected to Warm Ischemia. (July 2018) - Urbanellis, Peter; Hamar, Matyas; Kaths, Moritz; Linares, Ivan; Kollmann, Dagmar; Ganesh, Sujani; John, Rohan; Yip, Paul; Mucsi, Istvan; Ghanekar, Anand; Bagli, Darius; Konvalinka, Ana; et al.
Abstract : Background: Increasing evidence demonstrates the superiority of normothermic ex-vivo kidney perfusion (NEVKP) over cold storage (CS) for grafts sensitive to ischemia-reperfusion injury, including kidneys procured following donation-after-cardiac-death (DCD). To account for this improvement, we investigated whether NEVKP-preservation returns the genetic profiles of DCD grafts to that of unmanipulated naïve kidneys. Methods: Kidneys from 30kg Yorkshire pigs were removed following 30 minutes of warm ischemia in a model of DCD. These grafts were then stored in either static cold histidine-tryptophan-ketoglutarate solution (CS) or subjected to pressure-controlled NEVKP for 8 hours prior to heterotopic autotransplantation. Kidney biopsies were collected on POD3 and gene expression was compared with naïve porcine kidneys utilizing the Affymetrix GeneChip® Porcine Gene 1.0 ST Array platform examining over 23, 000 transcripts. Validation was performed using quantitative real-time polymerase chain reaction. Results: During NEVKP storage, DCD grafts demonstrated favourable perfusion characteristics including progressive lactate clearance (0hr: 10.29 +/-0.48 mmol/L vs 8hr: 1.67+/-0.67 mmol/L, n=5, P<0.01), decreasing intra-renal resistance (0hr:1.63+/-0.20 mmHg/mL/min vs 8hr:0.41+/-0.13 mmHg/mL/min, n=5, p<0.01), and continuous urine production. Post-transplantation graft function significantly improved with NEVKP compared to CS with decreased peak serum creatinine (POD1: 4.0+/-1.15mg/dL vs POD3: 12.0+/-0.78mg/dL, n=5, p<0.01) and higher creatinine clearance on POD3 (39.6+/-11.8mL/min vs 2.6+/-0.9ml/min, n=5, p<0.01). Genomic comparison of grafts subjected to NEVKP on POD3 showed significant differences in only 27 genes when compared to naïve porcine kidneys (Table 1, >±2-fold changes in expression over naïve, n=3, P<0.05, FDR p-value<0.20). In contrast, 668 genes were significantly differentially expressed between grafts stored with CS on POD3 and naïve kidneys (Table 2, >±2-fold changes in expression over naïve, n=3, P<0.05, FDR p-value<0.20). Conclusions: NEVKP restored damaged kidney grafts in a model of DCD with a genomic profile closely resembling naïve kidneys. Conversely, ongoing injury was evident in DCD grafts following CS through increased expression of genes related to inflammation, apoptosis, and repair. Together, these findings support the use of NEVKP for storage of DCD grafts that are more susceptible to ischemia-reperfusion injury.